Comparative study of intralesional tuberculin protein purified derivative (PPD) and intralesional measles, mumps, rubella (MMR) vaccine for multiple resistant warts. (29th October 2020) - Mohammed, Yaser F.; Ibrahim, Hany S.; Elbarbary, Marwa A.; Elsaie, Mohamed L.
Abstract: Background: Cutaneous warts are frequent conditions that possess much challenge to treat. Objective: To evaluate safety and efficacy of intralesional injection of tuberculin purified protein derivative (PPD) antigen injection vs MMR (mumps, measles, rubella) antigen for the treatment of multiple warts. Methods: The study included 90 Patients who were divided into three groups (A, B, and C). Each group consisted of (30) patients. Group (A) subjects received intralesional PPD injections. Group (B) subjects received intralesional MMR antigen injection and Group (C) received intralesional saline injection. Results: Full clearance of warts was observed in 18 (60%) of patients in group (A) (70%) vs 24 patients (80%) in group (B). Distal warts completely disappeared in 18 (60%) of patients in group A and 12 (40%) of patients in group B. Infrequent side effects including pain, erythema, and minimal induration were reported in both groups. Conclusion: We established a good safety and efficacy profile for tuberculin PPD and MMR antigens in resistant wart treatment.